Conocimiento Complementario “Innovación Social Quito” como avance práctico de desarrollo urbano y el modelo teórico "Ciudad del Futuro” - perspectivas de aprendizaje recíproco - Gierhake, Klaus; Justus Liebig University Giessen (My University, 2023)
Social innovations have been widely analyzed. It also have the typical elements of a spatial innovation process. The aspects of "improved learning, planning, use of local knowledge and improvement of local administrative processes" also include institutional development. This perspective is gaining enormous importance in the context of development agendas of many international organizations, Social innovation and the promotion of local governance will be examined under a special spatial perspective: metropolitan regions, using the example of Ecuador's capital, Quito. Results (include): a) There is unconnected knowledge and/or specialization on partial aspects in the large field of "social innovation and metropolitan development". b) Whether and to what extent an undervaluation of applied sciences is a cause for this state of scientific discussion remains to be discussed. c) There is obviously complementary knowledge between Europe and Latin America. The case-related progress from Ecuador can be further developed into first models on the basis of methods of applied geography.
Keywords: Lokales Wissen Städte; Soziale Innovation; Quito; Ecuador; Stadt der Zukunft; ddc:910